Advances in cultural entrepreneurship - Lockwood, Christi; Soublière, Jean-François (Research in the sociology of organizations, 2022)
United under the "cultural entrepreneurship" label, scholars have emphasized how entrepreneurship, strategic innovation, and organizational change are fundamentally cultural undertakings. Extant work in this vein has revealed how actors harness elements from their cultural milieu to secure the support of valued audiences, or undertake more profound changes to foster a cultural environment supportive of their endeavours. This volume aims to expand the agenda of cultural entrepreneurship research by celebrating (and advocating for) two promising advances. Section A aims to put culture in cultural entrepreneurship research. Early research identified storytelling as a first mechanism by which actors could gain audience support. More recently, however, scholars have grown interested in understanding additional manifestations of culture and modes of meaning-making. Moving in this fruitful direction, this section includes chapters that explore the multiple views on culture in cultural entrepreneurship research, and the multi-faceted ways by which culture shapes and is shaped by entrepreneurial action. Section B seeks to take cultural entrepreneurship beyond entrepreneurship. Early cultural entrepreneurship research has been predominantly confined to - and sometimes equated with - the study of new venture legitimation and resource acquisition. Making progress towards broadening the scope of what cultural entrepreneurship entails and can explain, this section encompasses theoretical and empirical investigations in a wide variety of empirical settings, illuminating how actors effect a range of outcomes.